2018
DOI: 10.1002/pc.24921
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitrogen–oxygen plasma functionalization of carbon nanotubes in epoxy nanocomposites

Abstract: Carbon nanotubes (CNTs) functionalization was carried out with radio frequency plasma in different working gas Ar/O2 and Ar/O2/N2 at different plasma powers to synthesize epoxy nanocomposites. After the CNT's had been treated, the Fourier transform infrared (FTIR) spectroscopy showed an additional peak at 1,740 cm−1, attributed to carboxylic groups, corroborating the X‐ray photoelectron spectroscopy that shows attachment of oxygen groups, which indicates CNTs' functionalization. Raman shows an increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…6 To improve the fracture toughness of epoxy, various nano-reinforcements have been investigated. 7 For example, typical nano-reinforcements involve zero-dimensional nanoparticles, such as titanium dioxide (TiO 2 ) and silica (SiO 2 ), 8,9 one-dimensional nanofibers, such as carbon nanotubes (CNTs), 10 and two-dimensional nanoplatelets, such as nanoclay and graphene. [6][7][8][9][10][11][12][13] Although these nanofillers can improve the fracture toughness of epoxy, many processing problems remain unsolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 To improve the fracture toughness of epoxy, various nano-reinforcements have been investigated. 7 For example, typical nano-reinforcements involve zero-dimensional nanoparticles, such as titanium dioxide (TiO 2 ) and silica (SiO 2 ), 8,9 one-dimensional nanofibers, such as carbon nanotubes (CNTs), 10 and two-dimensional nanoplatelets, such as nanoclay and graphene. [6][7][8][9][10][11][12][13] Although these nanofillers can improve the fracture toughness of epoxy, many processing problems remain unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…7 For example, typical nano-reinforcements involve zero-dimensional nanoparticles, such as titanium dioxide (TiO 2 ) and silica (SiO 2 ), 8,9 one-dimensional nanofibers, such as carbon nanotubes (CNTs), 10 and two-dimensional nanoplatelets, such as nanoclay and graphene. [6][7][8][9][10][11][12][13] Although these nanofillers can improve the fracture toughness of epoxy, many processing problems remain unsolved. 14,15 For example, a small amount of TiO 2 improves the fracture toughness of epoxy by crack deflection and crack pinning, yet agglomeration of the TiO 2 nanoparticles limits further improvement of the fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…These gases are ionized into a plasma reactor, forming highly reactive species that depending on the conditions of the plasma are grafted to a greater or lesser extent changing the surface chemistry of the NPs. As in the surface modification of polymers, oxygen plasma is also used to graft polar groups onto the surface of the NPs (e.g., hydroxyl, carbonyl, carboxyl) and improve their wettability [105][106][107], although noble gases such as Ar can also be used to activate the surface of the particles or generate vacancies or defects and then at a later stage (or combination of gases) chemical groups are grafted either by plasma or by traditional wet chemistry methods [108]. NPs that have been modified by plasma include carbon nanotubes (CNTs), carbon nanofibers (CNFs), graphite [109], graphite oxide, nanoclays [110], and metallic and non-metallic NPs [111,112].…”
Section: Treatment Of Nps Prior To Pncs Processingmentioning
confidence: 99%
“…These authors found that the plasma treatment formed carboxylic acids and also C-N bonds. As a result of this treatment, a better dispersion and distribution of CNTs was observed, resulting in an improvement of the PNCs mechanical properties [107]. In another work, the CNTs were functionalized in a plasma reactor with a cylindrical chamber of 40 cm in diameter and 30 cm in length, gap of 5 cm, using a RF source of 13.56 MHz and 200 watts (W) of power, during 60 min using air as working gas.…”
Section: Treatment Of Nps Prior To Pncs Processingmentioning
confidence: 99%
“…Up to now, many studies have been devoted to the analysis of surface plasma treated fiber-based [31] and carbon nanotubes [32][33][34] based composites but little has been devoted to the study of particulate polymeric composite containing plasma functionalized graphite/graphene.…”
Section: Introductionmentioning
confidence: 99%